Sistem Pendukung Keputusan Evaluasi Kinerja Kepala Dusun Menggunakan Integrasi Cocoso dan AHP - Safni Deliani; Triase Triase (Journal of Information System Research (JOSH), 2025)
Decision Support Systems (DSS) have become an important tool in various fields to assist complex and critical decision making. In Padang Tualang District, North Sumatra, evaluating the performance of hamlet heads is a big challenge because it is done manually and unsystematically, which often results in inaccuracies and unfairness in the assessment. This research aims to develop and implement a web-based SPK that integrates the COCOSO and AHP methods to evaluate the performance of hamlet heads more objectively and transparently. The research stages begin with problem identification, followed by data collection through observation and interviews, as well as data analysis using the COCOSO and AHP methods. The system is then designed and implemented, followed by testing using black-box methods to ensure its reliability and functionality. The results of this system show that Jusmianto is ranked first in the performance evaluation with the highest score with a score of 281,495. System testing shows that all features function as expected, both for admin and user users. It is hoped that the implementation of this SPK can improve the quality of leadership at the hamlet level and encourage equitable development in all sub-district areas.